A-23 Positive Associations between Cognition and Openness in HIV+ Individuals with Detectable Viral Loads. (30th August 2021) - Martin, Karli M; Del Bene, Victor A; Triebel, Kristen; Wheeler, Pariya; Vance, David
Abstract: Objective: High rates of medication non-adherence with the advent of combination antiretroviral therapy (cART) in the HIV+ population persist at approximately 50%. Consequences of non-adherence include higher mortality and transmission risk. As the population of older adults with HIV-associated neurocognitive disorder (HAND) increases, the relationship between cognition, personality, and medication adherence requires further study. We explore whether the five main personality traits were related to cognition and serostatus outcomes. Method: 186 HIV+ individuals completed a neuropsychological battery and the Big Five Inventory to measure personality. Viral load was dichotomized as undetectable (< 19; n = 128) and detectable (≥20; n = 58). Pearson correlations were used to evaluate the relationship between cognition and openness in undetectable and detectable groups. Results: Global cognition was positively associated with openness in both undetectable, r(126) = 0.24, p = 0.006, and detectable viral load groups, r(56) = 0.46, p < 0.001, with a moderate association observed in those with detectable viral loads. A moderate, positive relationship was found in the detectable group between openness and verbal ability (r(56) = 0.420, p = 0.001), immediate recall (r(56) = 0.404, p = 0.002), delayed recall (r(56) = 0.418, p = 0.001) and working memory (r(56) = 0.444, p < 0.001). In the undetectable group, openness was correlated with verbal ability, (r(126) = 0.296, p = 0.001), and processing speed (r(126) = 0.275, p = 0.002). Conclusion: In HIV+ individuals with detectable viral loads, increased openness is moderately associated with higher cognitive functioning. These associations were weaker in the undetectable group. HIV+ people who are open to new experiences have better cognitive functioning, which may be a viable intervention target to increase medication adherence.